Apathy evaluation scale-informant version in progressive supranuclear palsy: Psychometric properties and clinical correlates. (February 2023) - Cuoco, Sofia; Cappiello, Arianna; Carotenuto, Immacolata; Bisogno, Rossella; Abate, Filomena; Tepedino, Maria Francesca; Pellecchia, Maria Teresa; Erro, Roberto; Barone, Paolo; Picillo, Marina
Highlights: Psychometric properties of the Apathy Evaluation Scale-informant version in PSP. T he clinical correlates of apathy in PSP patients are described. The AES-I is a reliable and valid tool for the assessment of apathetic symptoms. Apathy may represent a marker of worse cognitive impairment at follow-up in PSP. The standardization of apathy studies in PSP is useful for diagnosis and intervention.